Can histopathological evidence of ankylosis of the tooth be helpful in the prevention of a medicolegal case in case of iatrogenic fracture of the mandible during dental extraction where preoperative radiographs have not been taken? - Samir D Khaire; Shameeka S Thopte; Shams U L Nisa; Kavita Wadde (Wolters Kluwer Medknow Publications, 2023)
A fracture of the mandible is a rare complication that can occur during a dental extraction being carried out under local/general anesthesia. It is always advisable to take a pre-operative radiograph of the tooth to be considered for extraction to study the root configuration and make a surgical plan for the case. Most of the dental extractions carried out without taking a preoperative radiograph are completed uneventfully. However, in rare cases, complications can arise owing to local anatomical variations and lead to medicolegal issues and litigation. This article discusses the management of a case of iatrogenic fracture of the mandible during dental extraction, wherein a pre-operative radiograph was not taken; however, following extraction of the tooth and management of the fracture mandible, the histopathology report of the extracted tooth was suggestive of ankylosis of the tooth.